2015
DOI: 10.1007/s00268-015-3383-z
|View full text |Cite
|
Sign up to set email alerts
|

EBSLN and Factors Influencing its Identification and its Safety in Patients Undergoing Total Thyroidectomy: A Study of 456 Cases

Abstract: Large goitres are not uncommon in toxic cases. The EBSLN is at highest risk of injury in this subgroup of patients and surgical expertise is essential to identify this entity of EBSLN to perform a safe thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
5
12
0
1
Order By: Relevance
“…Similar reports were published in 2016 by Ravikumar et al . [ 2 ] They classified goiters as large volume and small volume with a cutoff of 50 cc and they also reported a higher incidence of Type 2 nerves in large volume glands (89.4%). Type 2b nerves were more common in toxic (37.9%) than nontoxic lobes (5.46%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar reports were published in 2016 by Ravikumar et al . [ 2 ] They classified goiters as large volume and small volume with a cutoff of 50 cc and they also reported a higher incidence of Type 2 nerves in large volume glands (89.4%). Type 2b nerves were more common in toxic (37.9%) than nontoxic lobes (5.46%).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of EBSLN injury in patients undergoing thyroidectomy is reported to be up to 58%. [ 2 ] Different authors from time to time have tried to describe the anatomy of the EBSLN and its relation to the superior thyroid vessels and hence there are various surgical and anatomical classifications mentioned in literature for EBSLN. [ 3 4 ] However, the most widely accepted typing was proposed by Cernea et al .…”
Section: Introductionmentioning
confidence: 99%
“…Most of them did not find any statistical difference between elderly and young patients. Bergenfelz et al found instead a correlation between older age and permanent vocal cord palsy in a study conducted in 5,252 patients (21,22).…”
Section: Surgical Complicationsmentioning
confidence: 94%
“…[19] Literatürdetip 1'in %17-60, tip 2a'nın %17-59, Tip 2b'nin ise %10-56 arasında saptandığı bildirilmektedir. [20][21][22][23][24][25][26][27] Oranların geniş bir aralıkta olmasının nedenleri arasında; hastanın ağırlığı, tiroidin büyüklüğü, toksik ya da non toksik guatr varlığı, sinirin gözle veya sinir monitorizasyonu ile belirlenmesi ve çalışmanın genişliği gibi değişkenler vardır. Bu sınıflamaya gore büyük guatrlarda tip 2b oranı belirgin olarak fazla olup tiroidektomide üst kutup diseksiyonu sırasın-dadaha fazla yaralanma riski altındadır.…”
Section: Süperior Laringeal Sinirin Ekstrenal Dalıunclassified